Beyond the user experience: Evaluating a Digital Serious Game in Project Management - Lima, Fúlvia Fernanda de; Silva, Adriano Ednaldo da; Lira, Kaylane Gonçalves; Albuquerque, Eduardo Geber de Melo; Luna, Alexandre José Henrique de Oliveira (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2025)
Context: The project management classroom often relies on theoretical teaching methods. However, a gap exists between the demand for skilled project managers and the ability of traditional education to fully prepare students. Problem: A major challenge in education, including project management learning, is maintaining student engagement and knowledge retention. Traditional methods often struggle to replicate real-world complexities, resulting in a gap between theoretical knowledge and practical application. This study explores whether a serious game can effectively bridge this gap. Solution: Serious games emerge as a promising solution to enhance engagement and knowledge retention in various learning contexts. In this study, we evaluated a digital serious game to improve both the tool and the students' experience. IS Theory: The theory of organizational learning proposes that organizations can learn and adapt. Serious align with this theory by providing simulated environments for collaborative learning and practical experience. Method: The study utilizes a mixed-methods approach, combining quantitative and qualitative data collection techniques to evaluate a serious game by a group of project management students. Summarization of Results: The study found that the serious game was effective in engaging students and enhancing their understanding of project management concepts. Students reported positive experiences with the game, highlighting its ability to simulate real-world scenarios. The game also demonstrated potential for improving knowledge retention and practical skill development. Contributions and Impact on IS: Providing empirical evidence for the effectiveness of serious games in project management, the study can inform future research and practice in the field.